Analysis of the daylight performance of window integrated photovoltaics systems. (January 2020) - Sun, Yanyi; Liu, Dingming; Flor, Jan-Frederik; Shank, Katie; Baig, Hasan; Wilson, Robin; Liu, Hao; Sundaram, Senthilarasu; Mallick, Tapas K.; Wu, Yupeng
Abstract: Integrating photovoltaics into windows provides the possibility of including an additional function of energy production to a conventional building fenestration component. There is no doubt that electrical power can be generated on-site. However, the effect of PV windows on the indoor luminous environment of the space served by them has not been comprehensively researched. This paper investigated the daylight performance of integrating four types of photovoltaics (semi-transparent thin film Cadmium telluride (CdTe) solar cells with 10% and 50% transparency, crystalline silicon solar cells with and without crossed compound parabolic concentrators (CCPC)) to a window of a typical south-facing office under different Window-to-Wall Ratios (WWRs). Annual useful daylight illuminance (UDI), daylight uniformity ratio (UR) and daylight glare probability (DGP) have been analysed based on dynamic simulation using RADIANCE. The simulation results show that windows integrated with crystalline silicon cells and CCPC optics have the potential to provide best daylight availability when compared with standard double glazed windows and other tested PV window prototypes, if it is applied to rooms with large WWRs (e.g. 60% or 75% WWR) at high latitudes (e.g. city of Harbin). Its application also improves the uniformity of daylight spatial distribution and eliminates the risk of glare. Semi-transparent CdTe PV window with 10% transparency can also improve the percentage of working hours that fall into UDI500–2000lux range, however, it will result in the most sharp illuminance contrasts within the room. Applying all of these tested PV windows can effectively reduce the possibility of glare. Highlights: Window integrated PV provides daylight control in addition to energy generation. Comprehensive daylight analysis was undertaken for four different PV windows. Dynamic daylight metrics UDI, UR and DGP have been investigated using RADIANCE. The effect of different WWRs on PV windows' daylight performance was explored. PV windows can reduce the possibility of glare and maximise use the daylight.